2022
DOI: 10.3390/s22186963
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Twin Case Study on Automotive Production Line

Abstract: The manufacturing sector is one of the areas where the advantages of digital twin technology can benefit mostly. The product development, including its software, electronics, mechanics, and physical behavior, is included in the digital twin of the product. Furthermore, simultaneous data capturing from the sensors and data processing are also available in the digital twin. This enables each phase of the development cycle to be simulated, processed, and validated to discover the potential problems before the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This study [ 42 ] introduced the use of digital twin technology in the commercial production phase of an automotive production line. The study found that the use of digital twin technology led to a 6.01% increase in production line efficiency and an 87.56% reduction in downtime.…”
Section: Related Workmentioning
confidence: 99%
“…This study [ 42 ] introduced the use of digital twin technology in the commercial production phase of an automotive production line. The study found that the use of digital twin technology led to a 6.01% increase in production line efficiency and an 87.56% reduction in downtime.…”
Section: Related Workmentioning
confidence: 99%
“…In the automotive and aviation industries, the main part of the physical entity in a DT model is usually a production line or an assembly line, or a shop floor when the focus is on the manufacturing and assembly phases. For the automotive industry, Mendi et al [28] applied DT techniques to an automotive production line in the manufacturing phase. The production line is visualized by the game engine Unity and the data is analyzed by some data-driven methods of AI algorithms.…”
Section: A Design and Manufacturing Phasesmentioning
confidence: 99%
“…The purpose of using a digital twin is to improve the functionality and increase the efficiency of processes [9]. The digital twin is not only limited to focusing on one entity but can also be applied to entire systems, thus creating a broad approach to the digitized factories of the future [10][11][12].…”
Section: Introductionmentioning
confidence: 99%